Effect of In-Ovo Injection of L-Arginine on Age Embryo Died, Embryo Performance, and Chick Quality of Local Chicken - Taufik, M.; Sara, U.; Yunus, M.; Maruddin, F.; Azhar, M. (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study aims to determine the Effect of In-Ovo injection of L-arginine on age embryo died, embryo performance, and chick quality of local chicken. A total of 160 eggs were put into a semi-automatic incubator which has a temperature range of 37-38 oC with a relative humidity of 55-65%. The injected L-arginine solution has a concentration of 0.5% (m/v). In-Ovo Feeding treatment was divided into 4 groups, the first treatment was without injection (control), the second treatment was injection of 0.2 ml L-arginine solution 0.5% (m/v)/egg, the third treatment was injection of 0.4 ml L-arginine solution. 0.5% (m/v)/egg, and Fourth Treatment was injection of L-arginine solution 0.6 ml 0.5% (m/v)/egg. The results showed that embryo mortality and hatchability were lower with L-arginine injection treatment than without injection. All treatments showed no effect on extraembryonic fluid absorption, but there was an increase in embryo weight in the injection treatment 0.2, 0.4, 0.6 ml L-Arginine 0.5% /eggs 2,355 g, 2,577 g, 2,705, respectively. In conclusion, In-Ovo injection of L-arginine in local chicken eggs have a good effect (the beneficial effect) on embryo died and embryo performance. Injection 0.4 ml L-Arginine 0.5% /eggs improved Hatchability and NHCW.